Pengaruh Ulasan Online, Rating dan Tagline terhadap Pembelian dengan Kepercayaan Konsumen - Aini Nursafaah; Muhamad Wildan Khaerudin (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
The development of internet technology has significantly shifted consumer behavior from conventional to online purchasing, including through e-commerce platforms such as Tokopedia. Factors such as online customer reviews, customer ratings, and taglines play an important role in influencing purchase decisions, especially among Generation Z, the dominant users of digital platforms. However, consumer trust is a key intervening variable that can strengthen the influence of these three factors on purchasing decisions. This study aims to analyze the effect of online customer reviews, customer ratings, and taglines on consumer purchase decisions on Tokopedia, with trust as an intervening variable. The research method used is descriptive quantitative, with regression analysis and Sobel test employed to examine both direct and indirect effects among variables. The population in this study consists of Generation Z individuals residing in Kuningan Regency. The results show that online customer reviews, customer ratings, and taglines have a positive effect on trust, and each also has a positive impact on purchasing decisions. Furthermore, trust is proven to mediate the relationship between the independent variables and the purchase decision. Thus, the more effective the use of reviews, ratings, and taglines, the higher the consumer trust and purchasing decisions on the Tokopedia marketplace. These findings suggest that e-commerce businesses should pay close attention to these three factors as strategic elements in enhancing customer trust and encouraging purchase decisions in the future.